Do adolescents with cerebral palsy agree with their caregivers on their participation and quality of life?. Issue 2 (April 2018) - Büğüşan, Sema; Kahraman, Aysu; Elbasan, Bülent; Mutlu, Akmer
Abstract: Background: It is important to determine the quality of life (QoL) and level of participation in children with Cerebral Palsy (CP). Previous research has used reports from adolescents or caregivers, but there is no evidence that caregivers' reports accurately reflect the experiences of the adolescents they are interested in. Objective/Hypothesis: The aim of this study was to investigate whether a difference was present in the views of the adolescents and their caregivers regarding the participation and the quality of life of adolescents with CP, and to reveal the parameters creating such differences. Methods: The participation levels and QoL of the adolescents were evaluated separately by the caregiver and the adolescent using the Pediatric Outcomes Data Collection Instrument (PODCI). Results: A statistically significant difference was found in terms of caregivers and adolescents' scores of PODCI upper extremity (Z = −2, 560, p = 0, 008), transfer&basic mobility (Z = −3, 839, p = 0, 000), sports/physical functioning (Z = −3, 103, p = 0, 002), happiness (Z = −2, 420, p = 0, 016) and global functioning (Z = −3, 639, p = 0, 001). The children's scores were statistically significantly higher than caregivers'. It was found that there was a poor consistence in terms of caregivers and adolescents' scores of upper extremity (ICC = 0, 373, p = 0, 012), transfer/basic mobility (ICC = 0, 289, p = 0, 016), sport/physical functioning (ICC = 0, 359, p = 0, 009); moderate consistence in terms of those of global functioning (ICC = 0, 421, p = 0, 003). Conclusion: It was determined that caregivers and children's answers were not compatible with one another especially in terms of subjective assessments such as happiness and pain, which suggests that the consideration of caregivers or children in the assessment of subjective situations will change the results.